Leaf anatomy as a taxonomy tool for the identification of Brazilian native species of Chionanthus (Oleaceae) - Kolb, Kathleen L.; Gomes, Sandra M. A.; Lombardi, Julio A. [UNESP] (Elsevier B.V., 2020)
The genera Chionanthus is composed by around 100 species distributed worldwide, in tropical and temperate regions of Asia, Africa, Americas and Australia. In Brazil, Chionanthus is the most abundant genera among the Oleaceae family, with 11 species described, nine of them being endemic. The lack of distinctive morphological aspects hinders the identification of some of these species. The aim of this work is to use the leaf anatomy as a tool to the taxonomy of Brazilian native species of Chionanthus, focusing on displaying features that ease their identification. The anatomy of fully expanded leaves was analyzed from 10 species: Chionanthus crassifolius, C. ferrugineus, C. filiformis, C. fluminensis, C. greenii, C. micranthus, C. parviflora, C. subsessilis, C. tenuis and C. trichotomus. The samples, obtained from herborized plants, were rehydrated and cross-sections were made in the middle of the leaf blade, on the petiole and, also, both of the epidermis were dissociated. The occurrence of common anatomic features to Oleaceae were noticed, such as the presence of sclereids and glandular trichomes. The description of the leaf anatomy has permitted to determine the distinctive characteristics between species, such as the shape of the petiole, the vascular system arrangement in the petiole and in the midvein; the presence of papillate epidermal cells; cuticle ornaments; elongate glandular trichomes, sinuosity on the anticlinal walls of the epidermis, presence of hypodermis; differentiation of the mesophyll; and the contour of the midrib on the abaxial surface.
Keywords: Identification; Sclereids; Oleeae; Petiole anatomy; Domatia